Preparation and Performance of Mg2X-Based Thermoelectric Materials by MgH2 Reaction - Zhang, Yongzhong; Han, Yonghui; Chen, Shaoping; Meng, Qingsen (Asian Journal of Chemistry, 2014)
In the realm of thermoelectric materials, Mg2Si based thermoelectric materials have gained considerable attention from researchers in recent years due to their advantages of being non-toxic, eco-friendly and the fact that their elements are relatively abundant in nature. Oxidation and volatilization were effectively avoided in the preparation process of Mg2Sn using a field-activated and pressure-assisted sintering process to prepare high-purity Mg2Sn and Y-doped Mg2Sn thermoelectric materials. Test results showed that the doping of Y elements can improve the Seebeck coefficient and ZT values of Mg2Sn thermoelectric materials at low temperatures. Its best ZT value (0.033) was about three times that of pure Mg2Sn material (0.013) reported in literature. After doping Y in Mg2Sn material optimal temperature interval of its ZT value declined. These results hold important significance for the practical application of Mg2Sn materials.